Peran Pendidikan Ayah dalam Membentuk Karakter Islami Anak: (Studi Komparasi Penafsiran Wahbah Zuhaili dan Buya Hamka Dalam Q.S Luqman) - Nurkhaeriyah; Siti Hajar; Amalia Wulandari (PT. Pusmedia Group Indonesia, 2023)
Children are a gift and a trust entrusted by God to parents. And it is appropriate as parents should be able to maintain and educate their children to become children with morals and character. But many problems arise among children due to the less than optimal role of the family which is the first education for a child. The role of a mother is focused on the care of a child, while the role of a father is only limited to earning a living to meet the needs of his family. This research is intended to illustrate that a father must also participate in every child's development, especially in developing a child's character. One example that we can take in an effort to educate and build children's character is Luqman Al Hakim listed in Q.S Luqman. This research uses qualitative data, which is research produced in the form of descriptive which technically emphasizes on the study of text. While the interpretation method used by the author, is the muqarrin method, namely the comparison or comparative method. The results of this study conclude that the interpretation of Wahbah Zuhaili and Buya Hamka in the interpretation of Q.S Luqman has almost the same interpretation, namely Luqman's advice to his son about faith, birrul walidain filial piety and respect for parents, worship education (praying), carrying out amar ma'ruf nahi munkar, giving advice to his son not to have an arrogant nature. The role of a father in shaping a child's character is very important, if a child who lacks a father's affection will be vulnerable to experiencing a lameness in his development. While the difference between the interpretations of Wahbah Zuhaili and Buya Hamka is only in the way of delivery and the way of explanation because they use different styles. Keywords: Father Education; Children's Islamic Character; Wahbah Zuhaili; Buya Hamka.